2001
DOI: 10.1152/ajplung.2001.281.6.l1337
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lipid(s) bound to albumin increases endothelial electrical resistance: mimicked by LPA

Abstract: The objectives were to determine whether the permeability-decreasing activity of platelet-conditioned medium (PCM) is associated with a lipid bound to albumin and whether lysophosphatidic acid (LPA) is present in the PCM. A decrease in permeability was assessed by an increase in electrical resistance across endothelial cell monolayers derived from bovine pulmonary arteries and microvessels. The Sephacryl S-200 fraction of PCM that contained albumin, the albumin immunoprecipitate from the PCM, and the methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Our data agree with published reports that plateletreleased products decrease endothelial permeability (18) and increase TER (32). Although our data strongly support the concept that S1P is a platelet-derived factor that significantly underlies this effect, our data do not exclude the possibility that other platelet-derived products may also participate in the barrier-protective effect of platelets.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our data agree with published reports that plateletreleased products decrease endothelial permeability (18) and increase TER (32). Although our data strongly support the concept that S1P is a platelet-derived factor that significantly underlies this effect, our data do not exclude the possibility that other platelet-derived products may also participate in the barrier-protective effect of platelets.…”
Section: Discussionsupporting
confidence: 84%
“…Although our data strongly support the concept that S1P is a platelet-derived factor that significantly underlies this effect, our data do not exclude the possibility that other platelet-derived products may also participate in the barrier-protective effect of platelets. We and others have demonstrated that LPA, released from thrombin-stimulated platelets, possesses endothelial barrier-stabilizing activity (1,8,32). Although in our experiments LPA-induced endothelial barrier enhancement was weak in vitro (8), LPA released from platelets may form an active complex with serum albumin that further enhances its barrier-enhancing activity (32), which may in part explain the previously observed trypsin sensitivity of the barrier-enhancing platelet-derived factor (18).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations